2020
DOI: 10.21203/rs.3.rs-26834/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the effector mechanisms of Xuebijing Injection on COVID-19 based on network pharmacology.

Abstract: Objective: To examine the potential effector mechanisms of Xuebijing (XBJ) on coronavirus disease 2019 (COVID-19) based on network pharmacology.Methods: We searched Chinese and international papers to obtain the active ingredients of XBJ. Then, we compiled COVID-19 disease targets from the GeneCards gene database and via literature searches. Next, we used the SwissTargetPrediction database to predict XBJ’s effector targets and map them to the abovementioned COVID-19 disease targets in order to obtain potential… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…SF and XBJ inhibit inflammation and regulate immunity. XBJ also alleviated pneumonia-induced multi-organ damage [19,24]. LHQW significantly inhibited SARS-CoV-2 replication and diminished the cytokine release [13].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…SF and XBJ inhibit inflammation and regulate immunity. XBJ also alleviated pneumonia-induced multi-organ damage [19,24]. LHQW significantly inhibited SARS-CoV-2 replication and diminished the cytokine release [13].…”
Section: Discussionmentioning
confidence: 96%
“…Many studies have reported that TCM could resist viral pneumonia by modulating cytokine production, controlling viral replication, and regulating immunological function [22]. According to the COVID-19 seventh edition diagnostic criteria, four prescriptions, QFPD, LHQW, SF, and XBJ, achieved satisfactory results [13,19,23,24]. Among them, QFPD was reported to exhibit immune regulation, anti-infection, anti-inflammation and multi-organ protection by regulating toll-like receptors, NF-κB, and MAPK signaling pathways, which subsequently inhibits the release of pro-inflammatory factors [18,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Involving regulation of immunity [154], in ammatory cytokines [154][155][156][157][158][159][160] [190][191][192], virus infection [193][194][195][196][197][198][199][200][201][202][203], especially SARS-CoV-2 [196,[198][199][200][201][204][205][206], multi-organ (especially pulmonary) brosis [207][208][209][210] phospholipase C, gamma 1 (Plcg1) [219,220], in ammatory cytokines [221,222], virus infection, e.g., H1N1, HBV [223][224][225] Note: SARS-CoV-2, severe acute respiratory syndrome coronavirus-2; HTLV, human T-cell leukemia virus; HCV, hepatitis C virus; DHBV, duck hepatitis B virus; HBV, hepatitis B virus; H1N1, In uenza A virus H1N1 2009.…”
Section: Kegg Pathway Potential Role During Sars-cov-2 Infection Induced By Reported Evidence Nf-kappa B Signaling Pathwaymentioning
confidence: 99%
“…A real-world study noted that the incidence of adverse reactions to XBJ in clinical practice was low (0.3%) with most adverse reactions being mild. 8 Also, XBJ aids in the treatment of COPD 9 and AECOPD 10,11 due to its good effect in improving organ dysfunction and its anti-inflammatory. 12,13 and immune-modulating effects, 14,15 but its specific therapeutic mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%